Operando Studies for CO2/CO Reduction in Flow‐Based Devices - Lin, Zih‐Yi; Chang, Yu‐Chia; Chen, Yi‐Yu; Hsu, Yung‐Hsi; Peng, Kang‐Shun; Hung, Sung‐Fu (ChemNanoMat : chemistry of nanomaterials for energy, biology and more, 2024)
Electrocatalytic CO2 reduction reaction (CO2RR) conducted in a flow‐based device exhibits a substantial enhancement in Faradaic efficiency and catalytic current density compared to a conventional H‐type configuration. This highlights the distinct catalytic environment and behavior inherent in flow cells as opposed to H cells. To investigate the authentic properties of a catalyst within a flow‐based device, customized flow cells have been specifically devised for operando techniques during CO2RR and CORR, rather than resorting to an in‐situ three‐electrode H‐type configuration with its disparate catalytic environment and performance. This approach ensures a catalytic environment identical to that employed in electrochemical measurements. This review delineates the disparities between H‐type and flow‐based cells as well as the operando techniques tailored for flow‐based devices, including X‐ray absorption spectroscopy and Raman spectroscopy, preserving a consistent catalytic environment. It also compiles recent findings on copper‐based systems using operando flow‐based devices. The operando insights reveal a significant augmentation in catalytic current density, impacting both chemical properties and crystal structures. Furthermore, the observation of various catalytic intermediates enriches our comprehension. In essence, the application of operando techniques to flow‐based devices furnishes a comprehensive understanding of the catalytic behavior exhibited by diverse systems, propelling progress toward achieving Net Zero emissions. Authentic characteristics of a catalyst within a flow‐based device can be accurately acquired through operando techniques utilizing X‐ray absorption spectroscopy and Raman spectroscopy during carbon dioxide and carbon monoxide reduction reactions. This is achieved using specially designed flow cells where provide a catalytic environment identical to that employed in electrochemical measurements.